2022
DOI: 10.1093/jas/skac263
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of spent hemp biomass as a potential ingredient in ruminant diet: nutritional quality and effect on performance, meat and carcass quality, and hematological parameters in finishing lambs

Abstract: Spent hemp biomass (SHB), a byproduct of cannabinoids extraction from the production of industrial hemp has not been approved by FDA-CVM since its effects on animal health, performance, and product quality are unknown. Our objective was to investigate the effects of feeding two levels of SHB and a four-week withdrawal period on performance, carcass characteristic, meat quality and hematological parameters in finishing lambs. A total of 35 weaned, Polypay male lambs kept in single pens were randomly assigned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 120 publications
0
6
0
Order By: Relevance
“…Dry matter intake did not differ significantly, and mixing with silage masked the small amount of plant aroma of IHEEB, successfully eliminating the concerns of early scholars about low palatability and showing that cows can quickly adapt and accept the new unconventional feed ( 13 ). Although there were individual differences in dietary intake among the three groups, there did not seem to be much effect on the digestive properties of the diet, indicating that according to the total-tract apparent digestibility, IHEEB can be well-digested and absorbed by the intestinal tract of dairy cows.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Dry matter intake did not differ significantly, and mixing with silage masked the small amount of plant aroma of IHEEB, successfully eliminating the concerns of early scholars about low palatability and showing that cows can quickly adapt and accept the new unconventional feed ( 13 ). Although there were individual differences in dietary intake among the three groups, there did not seem to be much effect on the digestive properties of the diet, indicating that according to the total-tract apparent digestibility, IHEEB can be well-digested and absorbed by the intestinal tract of dairy cows.…”
Section: Discussionmentioning
confidence: 97%
“…Growing legalization and demand are anticipated to increase the global production of hemp and its byproducts ( 10 ). Currently, the research on industrial hemp and its processing byproducts mainly focus on the application of seed and hemp seed cake in livestock and poultry, which is considered to have a good application prospect ( 11 13 ). However, the application of industrial hemp ethanol extraction byproducts in dairy cows has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…This research suggests that endocannabinoids have the potential to improve dairy health and productivity by modulating feed intake, energy metabolism, and stress response in cows. Parker et al (2022) carried out an assessment of spent hemp biomass (SHB) as a potential ingredient in ruminant diet and mentioned that feeding SHB does not induce inflammation or affect the immune system, but it may have effects on metabolism, kidney function, and bone metabolism. It was found that feeding of SHB to lamb can have positive effects such as improved antioxidative status and better digestibility of the diet.…”
Section: Effects Of Hemp Feeding On the Performances Of Ruminant Animalsmentioning
confidence: 99%
“…CBD is the main non-psycotrophyc cannabinoid, while THC is the only psychoactive component in hemp. Even though industrial hemp has less than 0.2% of THC [5], this is a critical consideration for both consumers and industries because of the potential accumulation of THC in animal tissues and its effect on animal health, production, and food product quality [6,7]. In fact, it has been proved that cannabinoids of hemp by-products can transfer into milk when they are included in dairy cows' diet [8,9].…”
Section: Introductionmentioning
confidence: 99%